De l’îlot à l’enclos : l’immigration chinoise à San Francisco comme espace poétique (1910-1940) - Cécile Cormier (Anglophonia)
From 1910 to 1940, the Chinese who applied for immigration were disembarked and penned in on Angel Island (San Francisco Bay) where they were submitted to a medical examination and a thorough interrogation designed to determine whether their request should be granted. During their temporary detention, some wrote poems on the walls in Cantonese, which vented their helplessness and their anger, and literally inscribed their presence within a space that eluded and excluded them. Besides, the few who were allowed to immigrate generally passed from the confined space of the detention barracks to the enclosed space of Chinatown and its de facto limits. By exploring these poems and by referring to Chinese cosmology, I try to analyze how these men, whom American laws did not treat as men in their own right, managed to be part of the Sky-Earth-Man relationship on a territory that remained hostile to them or rejected them altogether.